Development and validation of a 3D-printed spectral verification system for colorimetric-based biosensors: DOI 10.14622/JPMTR-2006 - Balles, Jacqueline; Reiners, Robert; Spiehl, Dieter; Dörsam, Edgar; Blaeser, Andreas (Journal of Print and Media Technology Research, 2020)
We propose a method to transfer colorimetric assays based on gold nanoparticle aggregation from the laboratory to clinics, practices, or even to an application at home, by creating printed biosensors. While colorimetric assays need laboratory equipment and trained personnel, our printed biosensors (through manual pipetting) are storable, portable and usable from anyone anywhere. The method is verified using a model system for detection of the analyte amino acid cysteine (cys) and a spectral experimental setup in transmission. The model system consists of dispersed gold nanoparticles, which aggregate after cys addition. The biosensor is created by pipetting droplets of a gold nanoparticle solution onto the carrier Hostaphan GN 4600. Its functionality is sustained during the drying process through an addition of glucose, which preserves the gold nanoparticles from aggregation through its amorphous state. The glucose mixture can be kept amorphous over a long time by controlling the surrounding humidity with silica gel beads in an airtight container. The sample mount for the experimental setup is 3D-printed and designed to measure the spectral transmittance of the biosensor before and after analyte addition. The characterization of the setup suggests to expect coefficients of variation below 1 %, which validates its use. The biosensor and transmission spectrometer are tested with analyte concentrations between 10 mM and 50 mM. After a successful verification the printed biosensor would be ready to be evaluated without special equipment, meaning visually or with commercially available imaging techniques. Keeping in mind the possible application at home, the most obvious solution is using your own eyes or smartphone. These methods are discussed in the outlook. Keywords: spectrometer, gold nanoparticle aggregation, color change, ready to use, printed biosensor